1998
DOI: 10.1084/jem.188.11.1993
|View full text |Cite
|
Sign up to set email alerts
|

Stability and Diversity of  T Cell Receptor Repertoire Usage during Lymphocytic Choriomeningitis Virus Infection of Mice

Abstract: Numerous studies have examined T cell receptor (TCR) usage of selected virus-specific T cell clones, yet little information is available regarding the stability and diversity of TCR repertoire usage during viral infections. Here, we analyzed the Vβ8.1 TCR repertoire directly ex vivo by complementarity-determining region 3 (CDR3) length spectratyping throughout the acute lymphocytic choriomeningitis virus (LCMV) infection, into memory, and under conditions of T cell clonal exhaustion. The Vβ8 population represe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
107
3

Year Published

1999
1999
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(123 citation statements)
references
References 33 publications
13
107
3
Order By: Relevance
“…6A). Although NP118-specific T cells from RIP-NP mice demonstrated a slight increase in their frequency of new V␤ families such as V␤4 and V␤6, the dominant V␤ families still consisted mainly of V␤8.1/8.2 and V␤10, similar to that observed in BALB/c mice (16,34).…”
Section: Tcr V␤ Gene Family Usage By Low-and High-avidity T Cellsmentioning
confidence: 57%
“…6A). Although NP118-specific T cells from RIP-NP mice demonstrated a slight increase in their frequency of new V␤ families such as V␤4 and V␤6, the dominant V␤ families still consisted mainly of V␤8.1/8.2 and V␤10, similar to that observed in BALB/c mice (16,34).…”
Section: Tcr V␤ Gene Family Usage By Low-and High-avidity T Cellsmentioning
confidence: 57%
“…It has also been proposed that successive and repetitive stimulation upon chronic infection might be responsible for TCR repertoire narrowing (14,15). However, the idea of repertoire narrowing is not consensual either in experimental models or during HIV infection (16)(17)(18). In addition, it has been shown that the TCR repertoire directed against a particular CMV-derived epitope remained quite heterogeneous in healthy individuals (15).…”
mentioning
confidence: 99%
“…In addition, these cells are an important component of the immunity conferred by attenuated and recombinant viruses and by plasmid DNA vaccines. Although the kinetics of the antiviral CD8 ϩ T-cell response during the inductive and memory phases of certain systemic viral infections have been well characterized (8,16,19), there is little detailed knowledge about the kinetics of cellular immunity induced by conventional vaccines or by DNA immunization. Of particular interest is how rapidly CD8 ϩ T-cell responses develop after vaccination, as these cells play a critical role in limiting virus replication.…”
mentioning
confidence: 99%